Modelling and Analysis of Oscillating Water Column Based Wave Energy Converter with Compressed Air Energy Storage system - Sangar, S.; Arun Karthick, M.; Thiruvaran, T. (2023 IEEE Green Technologies Conference (GreenTech), 2023)
Using Wave Energy Converters as Distributed energy resources gained significant interest nowadays. A recent article from the US National Renewable Energy Laboratory introduced a concept called Distributed Embedded Energy Conversion Technology (DEEC-Tec). In this work a wave energy converter, with compressed air energy storage system and Oscillating Water Column principle, is proposed to be used as a DEEC-Tec. The proposed device addresses power quality issues associated with OWC devices. A Laboratory scale device was developed and tested. The device worked properly, however the produced output was low and recommendations to improve the device are given.
Keywords: Wave Energy Converter; DEEC-Tec; OWC; CEAS